Characteristics of all organic redox flow battery (AORFB) active species TEMPO-methyl viologen at different electrolyte solution - Ariyanti, Dessy; Purbasari, Aprilina; Hapsari, Farida Diyah; Saputra, Erwan Adi; Hamzah, Fazlena (Center of Biomass & Renewable Energy (CBIORE), 2024)
The practice of using wind and solar energy to generate electricity represents a solution that would be beneficial for the environment and ought to be explored. However, in order to ensure users' stability and continuous access to electricity, the increasing usage of renewable energy needs to align with the advancement of energy storage technologies. Redox flow batteries, which use an organic solution as the electrolyte and a proton exchange membrane as an ion exchange layer, are currently the subject of extensive research as one of the alternative renewable energy storage systems with the benefit of a techno economy. This study investigated the solubility of organic solution, namely 2,2,6,6-Tetramethylpiperidinyloxy or 2,2,6,6-Tetramethylpiperidine 1-oxyl (TEMPO) and methyl viologen (MV) in various essential electrolyte solutions such as NaCl, KCl, KOH, and H2SO4 that can be used as electrolytes of all organic redox flow battery (AORFB) system to produce high energy density and charging and discharging capacity. The result shows the optimum condition for effective charge transfer in AORFB is TEMPO catholyte and MV anolytes in the 0.08 M H2SO4electrolyte solution. Additionally, a correlation between the acquisition of electrolyte solutions on TEMPO catalyst and MV anolytes was discovered by the data. Electrolyte solution can improve electrical conductivity in TEMPO solution, which in turn can improve the efficiency of AORFB charging and discharging. Contrarily, MV anolytes exhibit a different pattern where the addition of electrolyte solutions reduces their electrical conductivity. RFBs systems with the aforementioned catholyte and anolyte can be used to store solar energy with a maximum current of 0.6 A for 35 minutes. Storage effectiveness is characterized by a change in colour in the catholyte and anolyte. The findings firming the possibility of using AORFB as one of the alternative energy storage systems that can accommodate the intermittence of the renewable energy input resource.